1996
DOI: 10.1007/bf00431087
|View full text |Cite
|
Sign up to set email alerts
|

Circulating immune markers in advanced renal cell carcinoma during immunotherapy with interferon gamma

Abstract: Circulating immune markers sICAM-1, sELAM-1, sMHC-I, beta 2-MG, sCD4 and sCD8 were evaluated prior to and during immunotherapy with biologically active doses of interferon gamma (IFN-gamma) in 16 patients with advanced renal cell carcinoma (RCC) over a period of 12 months. Compared to 20 healthy controls, significantly (P < 0.01) elevated baseline levels of circulating adhesion molecules sICAM-1 (mean 1166 vs 230 ng/ml) and sELAM-1 (70 vs 17 ng/ml) were found in all patients. Compared to responders (n = 2) or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…We demonstrated that NSCLC patients who achieved long-term disease control presented lower serum sCD8 at the end of cycles 2–4. Although no published papers assessed the circulating sCD8 levels in cancer patients on PD-1/PD-L1 inhibitors, lower baseline sCD8 was previously shown in responders to immunotherapy with interferon-alpha (IFN-α) [ 36 ] and higher on-treatment sCD8—in patients with progressive disease dosed with IFN-γ [ 37 ]. In contrast, other authors highlighted better outcomes with a higher baseline sCD8 [ 38 ] or a higher increase in serum sCD8 during treatment [ 39 ], but those patients were dosed with a different drug (interleukin-2, IL-2).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We demonstrated that NSCLC patients who achieved long-term disease control presented lower serum sCD8 at the end of cycles 2–4. Although no published papers assessed the circulating sCD8 levels in cancer patients on PD-1/PD-L1 inhibitors, lower baseline sCD8 was previously shown in responders to immunotherapy with interferon-alpha (IFN-α) [ 36 ] and higher on-treatment sCD8—in patients with progressive disease dosed with IFN-γ [ 37 ]. In contrast, other authors highlighted better outcomes with a higher baseline sCD8 [ 38 ] or a higher increase in serum sCD8 during treatment [ 39 ], but those patients were dosed with a different drug (interleukin-2, IL-2).…”
Section: Discussionmentioning
confidence: 99%
“…The ambiguous results could suggest that the direction of correlation between sCD8 levels and immunotherapy success is not that obvious and might depend on additional factors, such as a type of malignancy and the used immunomodulator. Accordingly, higher sCD8 levels were favorable in melanoma and renal cell carcinoma patients but only during treatment with IL-2 [ 38 , 39 ] and not with IFN-γ [ 37 ]. Moreover, different behavior of sCD8 was noted during immunotherapy with various drugs: there was a trend toward the sCD8 levels increasing after dosing with recombinant IL-2 [ 31 , 39 41 ] or successful treatment with IFN-γ [ 37 ], but a similar trend was not observed in our cohort (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation